Paparan Bahan Kimia Berbahaya dan Risiko Kesehatan Tinjauan Risiko Kesehatan Akibat Paparan Logam Berat Pestisida dan Bisfenol A BPA pada Populasi Rentan - Elisabet Wednesday purba; Triana Srisantyorini; Suherman Jaksa (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
Exposure to harmful chemicals in the environment, such as heavy metals (lead, mercury, and cadmium), pesticides, and Bisphenol A (BPA), is a growing global public health problem due to industrial activities, agriculture, and the use of chemical-based products in daily life. This study aims to analyze the health risks due to exposure to these chemicals in vulnerable populations through a systematic literature review approach. Data was collected from national and international scientific journals published in the 2015–2025 period through databases such as Google Scholar, PubMed, and ScienceDirect. The results of the study show that heavy metals have the main toxic effects in the form of neurological developmental disorders in children, decreased cognitive function, and damage to liver and kidney organs. Pesticides are associated with an increased risk of nervous system disorders, respiratory diseases, and some types of cancer such as leukemia. Meanwhile, BPA is known to play an endocrine disruptor role that can cause hormonal disorders, obesity, and reproductive problems. The population most vulnerable to these impacts are children as well as workers in the agricultural and industrial sectors due to the high intensity of exposure. The conclusion of this study confirms that exposure to hazardous chemicals has a significant impact on human health, so it is necessary to strengthen regulations, environmental monitoring, and public education to minimize future health risks.